The Results of the XIX International Congress of French sociologists: new approaches to the study of uncertainty - N. V. Litvak (Vestnik MGIMO-Universiteta, 2013)
The paper reviews the major speeches of leading scientists at the last Congress of the largest associations of French-speaking sociologists. Analyzed the most pressing problems and the processes described in the work of the scientific forum dedicated to new approaches to the study of uncertainty in almost all spheres of human life, society and the state.